10 Researching SARS-CoV-2 from home: maximising the benefit of the GOSH digital research environment during national lockdown. (30th November 2020) - Issitt, Richard; Booth, John; Briggs, Lydia; Bryant, William; Shah, Mohsin; Spiridou, Anastassia; Sebire, Neil J
Abstract : The 2019 novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19, characterised by potentially severe respiratory and gastrointestinal symptoms. As of early October 2020, there were around 34 million confirmed cases of COVID-19 and more than 1, 000, 000 associated deaths globally. Initial data indicated that COVID-19 affected children with fewer symptoms and less severe disease compared with adults, however more recently some have developed an unusual associated systemic inflammatory condition: paediatric inflammatory multisystem syndrome temporally related to SARS-CoV-2 infection (PIMS-TS). In the UK, Public Health England outlined a shielding strategy designed to protect those extremely vulnerable to SARS-CoV-2 infection, such as individuals who are immunocompromised. At the same time, the UK Government enforced a National Lockdown for all except key workers. As such, researchers were unable to continue working on site at hospitals and Universities. The web-based Digital Research Environment platform at GOSH made it possible for research on GOSH patients to continue despite those limitations. Even more, the efficient data integration processes that the DRE have implemented enabled a rapid extraction of COVID-19 related data from the GOSH EPR system to support initial research results. We were able to examine a cohort of paediatric patients, presenting to GOSH, with suspected COVID-19 or PIMS-TS to document their clinical characteristics and outcomes with regard to the presence of underlying medical conditions associated with vulnerability and to establish whether underlying conditions such as vitamin D deficiency were prominent in these patients. By analysing this data during the first wave, we were able to identify that apparently 'vulnerable' groups were not overrepresented in patients hospitalised with COVID-19 or PIMS-TS.